Negative Streamer Propagation in Nitrogen - Kadhim, Ghada S.; Khalaf, Thamir H. (Iraqi Journal of Science, 2022)
For the development of negative streamer, a one dimension simulation is presented when a negative electric field is applied at atmospheric pressure to a 4 mm gap in nitrogen. At applied electric fields of 55, 60, 65 and 70 kV/cm, streamer parameters were studied at various time intervals. The aim of this paper is to determine the minimum electric field that must be applied for stable propagation of negative streamer discharge in nitrogen gas. As functions of position and time, the calculations provide detailed electron and ion density predictions, electric fields and density of space charges. The time interval was with a nanosecond resolution. Using 8000 element mesh to resolve the characteristics of the streamer, spatial resolution over the separation of electrodes 4 mm was obtained. The results were obtained by solving the equation of continuity for electrons and ions and the Poisson equation solution.